A phase 3 safety study of fosnetupitant as an antiemetic in patients receiving anthracycline and cyclophosphamide: CONSOLE‐BC. Issue 8 (19th January 2022) - Matsuura, Kazuo; Tsurutani, Junji; Inoue, Kenichi; Tanabe, Yuko; Taira, Tetsuhiko; Kubota, Kaoru; Tamura, Tomohide; Saeki, Toshiaki
Abstract : BACKGROUND: Fosnetupitant (FosNTP), an intravenous neurokinin 1 receptor antagonist, demonstrated a favorable safety profile with a potentially low risk of injection site reactions (ISRs) and promising antiemetic efficacy in patients receiving cisplatin‐based highly emetogenic chemotherapy in a previous phase 2 study. We conducted a randomized, double‐blind safety study to evaluate the safety profile of FosNTP, including ISRs, in patients receiving doxorubicin‐cyclophosphamide or epirubicin‐cyclophosphamide (AC/EC) chemotherapy. METHODS: Patients scheduled to receive AC/EC were randomized 1:1 to receive 235 mg of FosNTP or 150 mg of fosaprepitant (FosAPR), both in combination with 0.75 mg of intravenous palonosetron and 9.9 mg of dexamethasone on day 1. The stratification factors were age category (<55 vs ≥55 years) and study site. The primary end point was the incidence of treatment‐related adverse events (TRAEs) with FosNTP. RESULTS: Overall, 102 patients were randomized to FosNTP (n = 52) or FosAPR (n = 50), and all were treated with the study drug and evaluated for safety. The primary end point, the incidence of TRAEs, was similar with FosNTP (21.2%; 95% confidence interval [CI], 11.1%‐34.7%) and FosAPR (22.0%; 95% CI, 11.5%‐36.0%), with any‐cause ISRs observed in 5.8% and 26.0% of patients, respectively, and treatment‐related ISRs observed in 0% and 10.0%, respectively. The overall (0‐120 hour) complete response (defined as no emetic event and no rescue medication) rate, standardized by age category in the full analysis set, was 45.9% (23 of 51 patients) with FosNTP and 51.3% (25 of 49 patients) with FosAPR. CONCLUSIONS: FosNTP demonstrated a favorable safety profile with a very low risk of ISRs in the AC/EC setting. Abstract : Fosnetupitant shows a favorable safety profile in patients receiving doxorubicin‐cyclophosphamide or epirubicin‐cyclophosphamide chemotherapy. As an intravenous neurokinin 1 receptor antagonist with a low risk of causing injection site reactions, fosnetupitant may be used for protecting patients with cancer from experiencing chemotherapy‐induced nausea and vomiting.